(untitled) (Communications in Computational Physics, 2021)
In this paper, a gas-kinetic scheme (GKS) method coupled with a three temperature kinetic model is presented and applied in numerical study of the Edney-type IV shock/shock interaction which could cause serious problems in hypersonic vehicles. The results showed very good agreement with the experimental data in predicting the heat flux on the surface. It could be obviously seen that the current method can accurately describe the position and features of supersonic jets structure and clearly capture the thermal non-equilibrium in this case. The three temperature kinetic model includes three different models of temperatures which are translational, rotational and vibrational temperatures. The thermal non-equilibrium model is used to better simulate the aerodynamic and thermodynamic phenomenon. Current results were compared with the experimental data, computational fluid dynamics (CFD) results, and the Direct Simulation Monte Carlo (DSMC) results. Other CFD methods include the original GKS method without considering thermal non-equilibrium, the GKS method with a two temperature kinetic model and the Navier-Stokes equations with a three temperature kinetic model, which is the same as the multiple temperature kinetic model in current GKS method. Comparisons were made for the surface heat flux, pressure loads, Mach number contours and flow field values, including rotational temperature and density. By Comparing with other CFD method, the current GKS method showed a lot of improvement in predicting the magnitude and position of heat flux peak on the surface. This demonstrated the good potential of the current GKS method in solving thermodynamic non-equilibrium problems in hypersonic flows. The good performance of predicting the heat flux could bring a lot of benefit for the designing of the thermal protection system (TPS) for the hypersonic vehicles. By comparing with the original GKS method and the two temperature kinetic model, the three temperature kinetic model showed its importance and accuracy in this case.